2018
DOI: 10.1111/sode.12288
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal, moderated mediation model of grit, engagement, and literacy achievement among dual language learners

Abstract: This short-term longitudinal study asked (a) how and for whom socioemotional factors like grit and emotional engagement predict later literacy achievement; and (b) if there are reciprocal effects between literacy and these socioemotional factors. An autoregressive crosslagged (ARCR) design included 3 time points over 4 months with an ethnic minority, dual language learner sample (n 5 142; 54% female; 75% Latina/o; M 5 9.47 years old). The procedure at each time point included teacher-reported student emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Furthermore, most existing studies of grit and engagement have used cross-sectional data. To date, there appears to be only one published longitudinal study and this shortterm (4-month) longitudinal study (O'Neal et al 2018) found a reciprocal relationship between grit and school engagement: grit predicted later school engagement, and in turn, school engagement predicted grit in the third wave. However, O'Neal and colleagues' study was limited to a sample of dual-language learners in primary school (thirdfifth grade).…”
Section: Grit Academic Achievement and Engagementmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, most existing studies of grit and engagement have used cross-sectional data. To date, there appears to be only one published longitudinal study and this shortterm (4-month) longitudinal study (O'Neal et al 2018) found a reciprocal relationship between grit and school engagement: grit predicted later school engagement, and in turn, school engagement predicted grit in the third wave. However, O'Neal and colleagues' study was limited to a sample of dual-language learners in primary school (thirdfifth grade).…”
Section: Grit Academic Achievement and Engagementmentioning
confidence: 78%
“…One speculation about the weak relationship between grit and achievement is that the influence of grit on achievement may go through engagement or other variables such as studying efforts, and motivations (Usher et al 2018). Indeed, recent studies have shown that school engagement mediates the relationship between grit and academic performance (O'Neal et al 2018). In sum, these findings are significant and remit messages that more studies from other cultures or contexts are needed to replicate the associations between grit and achievement; and more academic outcomes, not limited to the academic achievement and engagement, need to be studied in relation to grit in the future.…”
Section: Engagement As a Stronger Outcome Than Achievementmentioning
confidence: 99%
“…There has been a considerable body of literature showing how grit may relate to school-related performance and behaviors. Gritty students are more likely to have higher levels of general academic achievement among university students in the United States (Duckworth et al, 2007 ; Duckworth and Quinn, 2009 ; Akos and Kretchmar, 2017 ); high school students in mainland China (Li et al, 2018c ), secondary education students in the United States (Cosgrove et al, 2018 ; Park et al, 2018 ), Germany (Schmidt et al, 2019 ), Austria (Dumfart and Neubauer, 2016 ), and Russia (Tovar-García, 2017 ); course-specific academic achievement among military cadet samples in the United States (Mayer and Skimmyhorn, 2017 ); literacy achievement among primary school students (O'Neal et al, 2018 ); academic achievement in science in secondary school students in Australia (Hagger and Hamilton, 2019 ); performance in a national spelling bee contest (Duckworth et al, 2010 ); retention in selected undergraduate students in the United States (Saunders-Scott et al, 2018 ); academic engagement in selected university and high school students in the Philippines (Datu et al, 2016 , 2018b ); academic self-efficacy among university students in the Philippines (Datu et al, 2017a ) and the United States (Renshaw and Bolognino, 2016 ); generalized self-efficacy (Renshaw and Bolognino, 2016 ); intellectual self-concept among selected twin sample in the United States (Tucker-Drob et al, 2016 ); emotional engagement among dual language learners in the United States (O'Neal et al, 2018 ); school-related motivation among Filipino, American, and Mexican American students (Eskreis-Winkler et al, 2014 ; Yeager et al, 2014 ; Piña-Watson et al, 2015 ; Datu et al, 2018b ); learning engagement in selected mainland Chinese adolescents (Lan and Moscardino, 2019 ); test motivation among twins in the United States (Tucker-Drob et al, 2016 ); deliberate practice in optional and required practice in specific sports domains among selected athletes mostly from the North American context (Tedesqui and Young, 2017 ); satisfaction with e-learning systems among university students in Portugal (Aparicio et al, 2017 ); college satisfaction (Bowman et al, 2015 ); leadership skills among military cadets (Mayer and Skimmyhorn, 2017 ); mastery orientation (Tucker-Drob et al, 2016 ); meaningfulness of academic activities (Yeager et al, …”
Section: Performance Psychological and Physical Benefits Of Gritmentioning
confidence: 99%
“…Except for a few investigations that used longitudinal (O'Neal, 2018 ; O'Neal et al, 2018 ; Park et al, 2018 ; Jiang et al, 2019 ; Datu et al, 2020 ) and experimental (Lucas et al, 2015 ) research approaches, previous studies mainly relied on cross-sectional research designs in examining the role of grit in performance, optimal psychological, and well-being outcomes. Given that cross-sectional designs are prone to common method bias that can delimit the validity of such studies (Podsakoff et al, 2003 ), future investigations are encouraged to adopt longitudinal designs (e.g., cross-lagged panel and latent growth curve modeling approaches) to offer stronger evidence about the complex association of grit with desirable performance and well-being.…”
Section: Moving Forward With the Science Of Gritmentioning
confidence: 99%
“…These studies all found grit to be related to achievement; however, they did not adjust for students' previous achievement, meaning that they may have overestimated grit's predictive value. Three additional studies with the current DLL sample found that: (1) peer grit, not individual grit, was predictive of later literacy achievement (O'Neal, 2018a); (2) emotional engagement, not grit, was a significant mediator of the impact of stress on literacy (O'Neal, 2018b); and (3) emotional engagement mediated the impact of grit on later literacy, especially among older elementary students (O'Neal, Goldthrite, Weston Riley, & Atapattu, 2018).…”
Section: Grit and Achievementmentioning
confidence: 98%